Komparasi Komparasi Model Pembelajaran Sejarah di Kelas IPA dan IPS SMA Angkasa Adisutjipto - Ebma Yudhasatria; Ajat Sudrajat (Muróbbî: Jurnal Ilmu Pendidikan, 2018)
Revitalization of history learning for senior high schools in the 2013 Curriculum implemented in science and social classes could affect the use of learning models. Learning models had elements as learning approaches, strategies, methods, and media that had to be correctly customized and implemented. It encouraged the researcher to conduct research on comparison of history learning models in science and social classes in SMA Angkasa Indonesia. This research aimed to analyze similarities and differences between learning models used in science classes and that used in social classes under the “Indonesian History” subject study implemented in SMA Angkasa Adisutjipto Indonesia. This research was descriptive-qualitative research done by comparing history learning models and performed through interviews and observations in science and social classes. Research subjects consisted of the head of curriculum division, history teachers, and students from both science and social classes. Data were collected in forms of information from informants, field observations, and facts on documents gathered. Research findings indicated that history learning in science classes of SMA Angkasa was dominated by the use of linguistic (writing), logical-mathematical, and interpersonal (independent) intelligences. Suitable learning models for science students were problem-based learning, independent learning, exercises, tasking, causal-relationship reasoning regarding history materials, and contextual learning in history. Meanwhile, intelligence found in social classes of SMA Angkasa was dominated by linguistic, interpersonal, spatial (visual, imagination), and kinetic intelligences. Hence, suitable learning models for social students should have been in forms of cooperative learning (discussions, questions-answers); active, creative, effective, and fun learning; role-playing; and contextual and thematic learning